Book reviews - Sundback, Susan; Illman, Karl-Johan (Nordisk judaistik/Scandinavian Jewish Studies, 1991)
Den föränderliga identiteten: om identitetsförändringar hos den yngre generationen polska judar som invandrade till Sverige under åren 1968–1972 (Julian Ilicki, 1988) is reviewed by Susan Sundback.Yehezkel Kaufmann: ein Lebens-und Erkenntnisweg zur Theologie der hebräischen Bibel (Thomas Krapf, 1990) is reviewed by Karl-Johan Illman.Helvetesporten (Anja Lundholm, 1989) is reviewed by Karl-Johan Illman.Zionism in Sweden: its beginning until the end of World War I (Morton H. Narrowe, 1990) is reviewed by Karl-Johan Illman.